Human Stem Cell Therapy for the Cure of Type 1 Diabetes Mellitus (T1D): A Hurdle Course between Lights and Shadows - Riccardo Calafiore; Giovanni Luca; Francesco Gaggia; Giuseppe Basta (Endocrines)
Background: T1D is a severe metabolic disorder due to selective autoimmune pancreatic islet β-cell killing, which results in complete abrogation of endogenous insulin secretion. The affected patients, once the disease is clinically overt, must immediately undertake insulin supplementation according to intensive therapy regimens to prevent the onset of acute and chronic complications, some of them potentially lethal. Replacement of the destroyed β-cells with fresh and vital pancreatic endocrine tissue, either of the whole organ or isolated islets transplantation, started a few decades ago with progressively encouraging results, although exogenous insulin withdrawal was obtained in a minor cohort of the treated patients. The restricted availability of donor organs coupled with general immunosuppression treatment of recipients to avoid graft immune rejection may, at least partially, explain the limited success achieved by these procedures. Results: The introduction of pluripotent stem cells (either of human embryonic origin or adult cells genetically induced to pluripotency) that can be differentiated toward insulin secretory β-like cells could provide an indefinite resource for insulin-producing cells (IPCs). Conclusions: Because the use of human embryos may encounter ethical problems, employment of adult multipotent mesenchymal stem cells (MSCs) extracted from several tissues may represent an alternative option. MSCs are associated with strong immunoregulatory properties that can alter early stages of β-cell-directed autoimmunity in T1D, other than holding the potential to differentiate themselves into β-like cells. Lights and shadows of these new strategies for the potential cure of T1D and their advancement state are reviewed.